The Position of the Great Powers in International Judiciary - Krzan, Bartłomiej (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Professor Wolfke established his reputation as a great international lawyer at the very beginning of his academic career when examining the structure of international society. Despite the passing of time, the validity of Professor Wolfke’s insightful conclusions remain intact. They still provide a valuable background for scrutinizing the influence of the Great Powers on international courts. The respective analysis concentrates on two potential avenues of influence over international courts and tribunals to be exercised by the Great Powers: domination with regard to their composition and the intervention in the proceedings conducted in front of them.
Keywords: great powers; international courts and tribunals; composition intervention in the proceedings